Menguak Arti dan Makna Ukiran Toraja di Kampung Tonga Melalui Film Dokumenter - Maylvin Premier Gusmawan; Anthony Y. M. Tumimomor; Martin Setyawan (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Tonga Village is home to a significant number of carving craftsmen in North Toraja, who are renowned for their unique carving art. However, there is a growing concern that the younger generation is not fully aware of the cultural and historical significance of Toraja carvings. By employing qualitative research methods, including interviews, observation, and documentation, this study was able to identify several key issues. One such issue is the lack of regeneration of craftsmen, which has led to a decline in the number of individuals engaged in this practice. Additionally, there is a dearth of cultural socialization about Toraja carving in formal education, which has contributed to a lack of understanding about the significance and meaning of these motifs. In light of the aforementioned issues, there is a clear necessity for the establishment of an information medium that can elucidate the meaning and significance of Toraja carving in a comprehensive manner, with film serving as a potential conduit for such an endeavor. One potential solution is the use of a documentary film. The research method employed in this study is qualitative, employing a linear strategy as a creative strategy in media design. It is anticipated that the information will be conveyed in greater detail, in accordance with reality, and structured in a narrative that is aligned with the target audience, namely students and students. The implementation of the media will occur on a digital platform, thereby facilitating the dissemination of information on a wider scale and effectively increasing cultural knowledge through the use of attractive visuals, clear audio, and integrated narratives. The result of this research is the potential production of a documentary film that can function as a conduit of information, providing education to the community and thus serving as a resource for the public.